Collaborative Cloud Manufacturing: Design of Business Model Innovations Enabled by Cyberphysical Systems in Distributed Manufacturing Systems - Erwin Rauch; Sven Seidenstricker; Patrick Dallasega; Robert Hämmerl (Journal of Engineering)
Collaborative cloud manufacturing, as a concept of distributed manufacturing, allows different opportunities for changing the logic of generating and capturing value. Cyberphysical systems and the technologies behind them are the enablers for new business models which have the potential to be disruptive. This paper introduces the topics of distributed manufacturing as well as cyberphysical systems. Furthermore, the main business model clusters of distributed manufacturing systems are described, including collaborative cloud manufacturing. The paper aims to provide support for developing business model innovations based on collaborative cloud manufacturing. Therefore, three business model architecture types of a differentiated business logic are discussed, taking into consideration the parameters which have an influence and the design of the business model and its architecture. As a result, new business models can be developed systematically and new ideas can be generated to boost the concept of collaborative cloud manufacturing within all sustainable business models.